Audience perception of humorous content in shaping brand awareness (case study of TikTok account @teammafiapentol.sub) (BIS Humanities and Social Science, 2026)
The rise of social media, particularly TikTok, has transformed digital marketing communication, with humorous content becoming a key strategy to attract attention and build emotional connections between brands and audiences. This study examines how audiences interpret humorous content and its relationship with brand awareness on the local culinary account @teammafiapentol.sub. Grounded in humour appeal theory and the brand equity model, the findings show that culturally embedded and absurd humor enhances emotional engagement while strengthening brand memory and associations. Using a descriptive qualitative approach within a post-positivist paradigm, data were collected through purposive in-depth interviews with five actively engaged followers and analysed thematically to identify patterns of humor interpretation and brand perception. Results reveal that brand recognition is reinforced through a distinctive mix of absurd situational humor, vernacular linguistic play, and improvisational creator–audience interaction that defines the account’s content style. Overall, the study highlights practical implications for emotional branding strategies in short-form video platforms for contemporary digital marketing communication contexts globally.